Silica-modified SnO2-graphene "slime" for self-enhanced li-ion battery anode. (April 2017) - He, Haiyong; Fu, Wei; Wang, Hongtao; Wang, Hong; Jin, Chuanhong; Fan, Hong Jin; Liu, Zheng
Abstract: Tin oxide is an attractive anode material for lithium battery, on the grounds of its high capacity (above 2000 mAh/g), environmental friendliness and low cost. However, the large volumetric expansion (>200%) and aggregation of lithium-tin alloy cause significant capacity fading after only a few hundred cycles. In this work, we design a new type of SnO2 based composite electrode to address the above two issues. SnO2 nanoparticles uniform anchored on graphene are covered by a thin layer of silica. Upon cycling, tin can diffuse into the coating layer and also spread laterally on the graphene surface to form a continuous thin film of Li2 Snx SiO3+y . Such design diminishes the volumetric expansion of individual Sn particles and aggregation of lithium-tin alloy, but also dramatically decreases the lithium transport distance and diffusion barrier. Additionally, we propose that diffusion-induced defects on surface offer capacitive-like regions to absorb extra lithium ions. As a result, this unique structure can maintain a high capacity of 1950 mAh/g after 1000 cycles at a specific current of 500 mA/g with negligible capacity loss, and excellent reversibility with a columbic efficiency retention over 99%. Graphical abstract: Silica is used to modify SnO2 -loaded rGO, where Sn can diffuse into silica to plate on rGO, avoiding the aggregation of tin-lithium alloy. The silica-modified SnO2 /graphene exhibits high capacity of mAh/g at 500 mA/g after 1000cycles. Highlights: An interfacial engineering method is used to obtain self-stainable silica modified SnO2/G nanosheet. Tin elements can diffuse into silica and along G to finally plate on G during cycling. Aggregation of LiSn alloy was effectively avoided. High specific capacities (>1950 mA h/g at a current density of 500 mA/g) can be maintained up to 1000 cycles without clear fading.